PROSPECTS OF THE DEVELOPMENT OF THE SERVICES OF ACCOMMODATION FACILITIES - Sarvinoz Toyirova (Journal of new century innovations, 2023)
Abstract: Each of us has encountered service in hotels more than once. It is about providing a high quality of service for guests, which should satisfy their needs and desires. Good service in a hotel is not only about providing a comfortable stay, but also creating a positive impression for visitors. Service in hotels is a set of services provided to guests during their stay at the hotel. It includes not only the provision of a comfortable room, but also catering, room cleaning, landscaping, and even the provision of leisure activities. This paper aims to help fill the gap by exploring what is included in the concept of service in a hotel, what are its advantages, and how to properly organize it.